THE IMPLEMENTATION OF NEW NORMAL POLICIES DURING THE COVID-19 PANDEMIC IN KENDARI CITY, SOUTHEAST SULAWESI, INDONESIA: KNOWLEDGE, ATTITUDES AND PRACTICE - Juminten Saimin; Nur Indah Purnamasari; Hartati Hartati (Public Health of Indonesia)
Background: The new normal policy during the COVID-19 pandemic requires public participation. Efforts to suppress the number of cases require knowledge, attitudes and behavior towards health protocols to prevent COVID-19.